Then and Now: New Examinations of the Sixties - Hewitt, Steve (Labour / Le Travail, 1999)
The article reviews and comments on the books, "The Other Side of the Sixties: Young Americans for Freedom and the Rise of Conservative Politics," by John A. Andrew III, "Blues for America: A Critique, A Lament, and Some Memories," by Doug Dowd, "The Way the Wind Blew: A History of the Weather Underground," by Ron Jacobs, "Living Inside Our Hope: A Steadfast Radical's Thoughts on Rebuilding the Movement," by Staughton Lynd, and "Direct Action: Radical Pacifism from the Union Eight to the Chicago Seven," by James Tracy.

September 1931: A Re-Interpretation of the Royal Canadian Mounted Police's Handling of the 1931 Estevan Strike and Riot - Hewitt, Steve (Labour / Le Travail, 1997)
Reassesses the 1931 Estevan miners' strike and riot in light of internal RCMP reports recently released under the federal Access to Information Act. Discusses reporting by local police officials at the time, which was more nuanced and sympathetic to the miners than had previously been believed. However, the RCMP was also under heavy pressure from higher authorities and mine owners to crack down. Three miners were killed (one died in hospital) and eight others injured by the police in a violent confrontation on September 29, 1931. A photograph is reproduced of the common grave where the three miners were buried under the epitaph, "Murdered by RCMP."
Keywords: ESTEVAN (Sask.); HEWITT, Steve; LABOUR/LE Travail (Book); Miners; ROYAL Canadian Mounted Police; Riots; SASKATCHEWAN; STRIKES & lockouts